S SISTEM INFORMASI AKUNTANSI KEUANGAN UNTUK MENGANALISA KESEHATAN PERUSAHAAN BERBASIS WEB - Sri Wahyuning Sri (Universitas Sains dan Teknologi Komputer, 2022)
The use of sophisticated technology is very much needed by the company as a support for the success and success of a plan that the company wants. The financial report is an information medium that records, summarizes a company's activities and is used to report the company's state and position to interested parties, especially creditors, investors and the company's management itself. Financial ratio analysis helps determine whether the company's financial performance is good or not. Financial ratio analysis can be classified into various types, some of which are liquidity, solvency, activity, and profitability ratios. The financial management system at the food market eat and eat Paragon Mall still uses a simple and less effective system (Microsoft Excel) because it still uses excel formulas and logic if using the formula incorrectly will result in errors in recording financial statements. The method used really takes a long time so that it is often not timely and the way to analyze it is only with profit and loss and the profits are written in the table. The financial ratio method is the main tool for conducting financial analysis and has several uses. Financial ratios show a systematic relationship in the form of comparisons between estimates (posts) of financial statements. With the existence of a financial reporting system to analyze the health of the company, it can help determine the profit for each period, so that the structure of the company's financial health can provide clearer information. Keywords: Financial Statements, Financial Ratios, Performance